ABDOMINAL SCENT GLAND OF METACANTHUS PULCHELLUS DALL. (HETEROPTERA : BERYTIDAE) - DHIMAN, S.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Single, median abdominal scent gland is observed situated in the third segment of dorsal side just below the tergum. It opens outside on the mid dorsal line by an Ostiole at the anterior margin of fourth abdominal segment. The apparatus comprises of gland proper, a reservoir and a reservoir duct. The gland cells lie all around the reservoir surrounded by adipose tissue. Diagonal muscle bundles controls the flow of secretion to go out through Ostiole. Scent fluid is acidic having pH 5.5. The gland remains active not only in nymphs but also in adults.